First principles study of oxidation of Si-segregated α-Ti(0001) surfaces. (16th November 2017) - Bhattacharya, Somesh Kr.; Sahara, Ryoji; Kitashima, Tomonori; Ueda, Kyosuke; Narushima, Takayuki
Abstract: The oxidation of the α-Ti(0001) surface was studied using the density functional theory. To enhance the oxidation resistance, we substituted Ti atoms with Si atoms on the Ti(0001) surface. We observed that Si prefers to segregate at the surface layer of Ti(0001) compared with other subsurface layers. The Si solubility on the Ti(0001) surface, based on the segregation energy, was found to be much larger than the corresponding bulk solubility. Si segregation was found to reduce the binding between the oxygen atom and the Ti(0001) surface and hinder the diffusion of oxygen atoms into the slab. The dissociation of the oxygen molecule on the clean and Si-segregated surfaces of Ti was found to be barrierless. Overall, the Si segregation on the Ti(0001) surface was found to hinder the dissolution of oxygen in Ti.